Pilus of Streptococcus pneumoniae: structure, function and vaccine potential - Miao, Chenglin; Cui, Yali; Yan, Ziyi; Jiang, Yongmei (Frontiers in Cellular and Infection Microbiology, 2023)
The pilus is an extracellular structural part that can be detected in some Streptococcus pneumoniae (S. pneumoniae) isolates (type I pili are found in approximately 30% of strains, while type II pili are found in approximately 20%). It is anchored to the cell wall by LPXTG-like motifs on the peptidoglycan. Two kinds of pili have been discovered, namely, pilus-1 and pilus-2. The former is encoded by pilus islet 1 (PI-1) and is a polymer formed by the protein subunits RrgA, RrgB and RrgC. The latter is encoded by pilus islet 2 (PI-2) and is a polymer composed mainly of the structural protein PitB. Although pili are not necessary for the survival of S. pneumoniae, they serve as the structural basis and as virulence factors that mediate the adhesion of bacteria to host cells and play a direct role in promoting the adhesion, colonization and pathogenesis of S. pneumoniae. In addition, as candidate antigens for protein vaccines, pili have promising potential for use in vaccines with combined immunization strategies. Given the current understanding of the pili of S. pneumoniae regarding the genes, proteins, structure, biological function and epidemiological relationship with serotypes, combined with the immunoprotective efficacy of pilins as protein candidates for vaccines, we here systematically describe the research status and prospects of S. pneumoniae pili and provide new ideas for subsequent vaccine research and development.